Efektifitas Abu Sekam Padi Dan Poly Aluminium Chloride Dalam Menurunkan Zat Warna Limbah Cair Industri Sasirangan - Luqman Nur Hakim; Syarifudin A.; Sulaiman Hamzani (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2016)
Abstract: Effectiveness Of Rice Husk Ash And Poly Aluminum Chloride In Reducing Exposure Colour Liquid Waste Industry Sasirangan. Sasirangan fabric industry is the textile of industry in Kalimantan Selatan produce wastewater of dyeing cloth sasirangan process that uses water as a primary adjuvant in stage process.The study aims to determine the effectiveness of rice husk ash and Poly Aluminium Chloridereduce levels of dyes in wastewater sasirangan